2023
DOI: 10.1007/s10514-023-10136-2
|View full text |Cite
|
Sign up to set email alerts
|

Large language models for chemistry robotics

Naruki Yoshikawa,
Marta Skreta,
Kourosh Darvish
et al.

Abstract: This paper proposes an approach to automate chemistry experiments using robots by translating natural language instructions into robot-executable plans, using large language models together with task and motion planning. Adding natural language interfaces to autonomous chemistry experiment systems lowers the barrier to using complicated robotics systems and increases utility for non-expert users, but translating natural language experiment descriptions from users into low-level robotics languages is nontrivial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…However, the translation of natural language experiment descriptions into low-level robotics languages presents significant challenges. 54 Recent advancements have utilized large language models to generate task plans, but reliably executing these plans in the real world using embodied agents remains a considerable hurdle. To enable autonomous chemistry experiments and reduce the workload of chemists, robots must interpret natural language commands, perceive the workspace, autonomously plan multistep actions and motions, consider safety precautions, and interact with various laboratory equipment.…”
Section: Role Of ML and Ai: Optimizing Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the translation of natural language experiment descriptions into low-level robotics languages presents significant challenges. 54 Recent advancements have utilized large language models to generate task plans, but reliably executing these plans in the real world using embodied agents remains a considerable hurdle. To enable autonomous chemistry experiments and reduce the workload of chemists, robots must interpret natural language commands, perceive the workspace, autonomously plan multistep actions and motions, consider safety precautions, and interact with various laboratory equipment.…”
Section: Role Of ML and Ai: Optimizing Synthesismentioning
confidence: 99%
“…The integration of natural language interfaces into autonomous chemistry experiment systems aims to simplify the use of complex robotics systems, making them more accessible to nonexpert users. However, the translation of natural language experiment descriptions into low-level robotics languages presents significant challenges …”
Section: Components Of Fully Automated Systemsmentioning
confidence: 99%
“…Progress in this area is already underway, exemplified by initiatives from companies like Hugging Face which have showed that it is possible to use LLMs as a controller to manage existing AI models to solve sophisticated AI tasks in different modalities and domains. [8] Examples in material science where LLMs are connected to robotic experimentation are still few but include recrystallization experiments, [107] successful performance of catalysed cross-coupling reactions, [108] and synthesis of humidity colorimetric sensors. [109] The reports currently available on this topic has the character of initial proofof-concepts but provide an indication of where we may be heading.…”
Section: The Fourth Rung: Orchestration and Autonomymentioning
confidence: 99%
“…Another way to screen target materials is through high-throughput experiments, which deepen the understanding of experimental work and improve catalysts through automated experiments. 17 However, this approach is challenging to implement for scholars lacking automated laboratories, as any successful step in synthesis and testing takes at least 1−2 days, and evidently, a large number of experiments are impractical for manual operation. Therefore, we aim to rely solely on DFT, conducting accurate and rapid screening work based on established research foundations.…”
mentioning
confidence: 99%
“…The main reason is that machine learning requires a significant accumulation of early stage data, and the total time consumption may even exceed that of high-throughput experiments. , Its lack of specificity has long been pointed out by scholars. Another way to screen target materials is through high-throughput experiments, which deepen the understanding of experimental work and improve catalysts through automated experiments . However, this approach is challenging to implement for scholars lacking automated laboratories, as any successful step in synthesis and testing takes at least 1–2 days, and evidently, a large number of experiments are impractical for manual operation.…”
mentioning
confidence: 99%